PROPOSAL OF SCALE DIAGRAMMATIC FOR QUANTIFICATION OF CERCOSPORA OF BEET - MAY DE MIO, Louise Larissa; OLIVEIRA, Ricardo Augusto de; Veiga FLORIANI, Andrea Mayer; SCHUBER, Joselia Maria; POLTRONIERI, Alex Sandro; ARAUJO, Marla Alessandra de ARAUJO; TRACH, Renato (Scientia Agraria, 2008)
Cercospora leaf. Spot (Cercospora beticola) is present in almost all fields where beet (Beta vulgaris) is cultivated and it can cause sugar yielding loss up to 40%. The aim of this work was to design and validate a diagrammatic scale for this disease. For the design of the diagrammatic scale, 95 sugar beet leaves were collected randomly in the metropolitan region of Curitiba, PR. The maximum and minimum proportions of damaged leaf area were considered and the intermediate levels of severity were determined according to "Weber and Fechner’s Stimulus Law". The proposed validation of the diagrammatic scale was conducted from 35 sugar beet leaves with different levels of severity, with and without the proposed diagrammatic scale. The use of the scale provided more accuracy and precision in the visual estimates, being indicated in epidemiological studies and may provide more accurate information in order to develop management strategies for the beet’s Cercospora leaf. Spot